Understanding the dose–response relationship of allopurinol: predicting the optimal dosage. (December 2013) - Graham, Garry G.; Kannangara, Diluk R. W.; Stocker, Sophie L.; Portek, Ian; Pile, Kevin D.; Indraratna, Praveen L.; Datta, Indira; Williams, Kenneth M.; Day, Richard O.
<x xml:space="preserve">Abstract</x> Aims The aim of the study was to identify and quantify factors that control the plasma concentrations of urate during allopurinol treatment and to predict optimal doses of allopurinol. Methods Plasma concentrations of urate and creatinine (112 samples, 46 patients) before and during treatment with various doses of allopurinol (50–600 mg daily) were monitored. Non‐linear and multiple linear regression equations were used to examine the relationships between allopurinol dose (D), creatinine clearance (CLcr) and plasma concentrations of urate before (UP) and during treatment with allopurinol (UT). Results Plasma concentrations of urate achieved during allopurinol therapy were dependent on the daily dose of allopurinol and the plasma concentration of urate pre‐treatment. The non‐linear equation: UT = (1 – D/(ID50 + D)) × (UP – UR) + UR, fitted the data well (r2 = 0.74, P < 0.0001). The parameters and their best fit values were: daily dose of allopurinol reducing the inhibitable plasma urate by 50% (ID50 = 226 mg, 95% CI 167, 303 mg), apparent resistant plasma urate (UR = 0.20 mmol l−1, 95 % CI 0.14, 0.25 mmol l−1). Incorporation of CLcr did not significantly improve the fit (P = 0.09). Conclusions A high baseline plasma urate concentration requires a high dose of allopurinol to reduce plasma urate below recommended concentrations. This dose is dependent on only the pre‐treatment plasma urate concentration and is not influenced by CLcr.